Change With Confidence : Answers to the 50 Biggest Questions that Keep Change Leaders Up at Night - Buckley, Phil (Your Coach Digital, 2017)
If you have been charged with leading a change initiative, chances are you were chosen for the job--that is, you didn't volunteer, but rather were tapped to lead or manage a large change project. You may have been given a short briefing and left to your own devices to succeed or fail in an uncertain, often threatening, environment. You may find yourself struggling to adapt your skill set to unfamiliar and anxiety-inducing conditions, conscious that your performance will affect your future career paths.Change with Confidence addresses the 50 biggest questions that change leaders ask time and again, and provides the context, examples, and advice to answer them well, and to enable successful, sustainable change. Whether you're trying to figure it out, are in the planning stage, are actively managing or are working to make it stick, you'll find guidance for a wide range of issues, including:Analyzing previous change initiatives to see what worked, what didn't, and whyFinding out who can influence your success or failure, help you, or trip you upDetermining what resources you'll need and how to get themOvercoming change fatigue and opposition to change.Although every change has its own circumstances, there are proven processes, tactics, and behaviors that lead to lasting success. Change with Confidence offers practical, experience-based advice on a difficult and stressful challenge.